Robotic and Endoscopic Thyroid Surgery: Evolution and Advances - Tae, Kyung; Ji, Yong Bae; Song, Chang Myeon; Ryu, Junsun (Clinical and experimental otorhinolaryngology, 2019)
To minimize surgical morbidity and neck scarring, minimally invasive thyroidectomy and robotic/endoscopic thyroidectomy via cervical, axillary, anterior chest, breast, postauricular or transoral approaches have been developed over the past 20 years. In this article, we review the evolution of robotic and endoscopic thyroid surgery and recent advances. Among remote access approaches, the gasless transaxillary approach, bilateral axillo-breast approach, postauricular facelift approach, and transoral vestibular approach are in common use today. Each procedure has its own advantages and disadvantages. Therefore, we need to understand these advantages and limitations, and to select the appropriate method for each patient. The most significant advantage of remote access thyroidectomy is its excellent cosmesis. The complication rate is similar in patients undergoing a remote access approach and those undergoing conventional surgery if the former is performed by experienced surgeons. Operative time is significantly longer in remote access thyroidectomy. In conclusion, remote access thyroidectomy is feasible and its outcomes are comparable to those of conventional transcervical thyroidectomy in highly selected patients.